Групування методів оцінки економічної безпеки підприємства - Тютченко, С. М. (My University, 2019)
Проаналізовано найбільш поширені методи оцінки економічної безпеки підприємства; запропоновано групування методик залежно від типу використання апарату для досліджень та розрахунків показників

In today's conditions, the economy of Ukraine is undergoing serious qualitative and quantitative changes that cause a number of problems in the field of management of a business entity. Economic security is a qualitative characteristic of the economic system of the economic entity, which determines its ability to maintain normal operating conditions, stable resource provision, as well as the consistent realization of the interests of owners and the state. Under economic security, the level of protection of all types of en-terprise's potential from internal and external threats is understood, which ensures its stable functioning and effective development. The content of this concept includes a system of tools that ensure competi-tiveness and economic stability of the enterprise. In this article the existing methods of assessing the economic security of the enterprise, which are most widely used in domestic enterprises. The author proposes the grouping of techniques depending on the type of use of the apparatus for research and calculation of indicators: indicator methods, methods for assessing the use of resources, expert estimation methods, methods of the theory of economic risks
Grouping of evaluation methods of economic safety of the enterprise
Keywords: економічна безпека; підприємство; ефективність управління; економічні показники; потенціал економічної безпеки; economic security; enterprise; efficiency of management; economic indicators; potential of economic security